A proposal of Brazilian Society of Surgical Oncology (BSSO/SBCO) for standardizing cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) procedures in Brazil: pseudomixoma peritonei, appendiceal tumors and malignant peritoneal mesothelioma - Batista,Thales Paulo (2017)
ABSTRACT Cytoreductive surgery plus hypertermic intraperitoneal chemotherapy has emerged as a major comprehensive treatment of peritoneal malignancies and is currently the standard of care for appendiceal epithelial neoplasms and pseudomyxoma peritonei syndrome as well as malignant peritoneal mesothelioma. Unfortunately, there are some worldwide variations of the cytoreductive surgery and hypertermic intraperitoneal chemotherapy techniques since no single technique has so far demonstrated its superiority over the others. Therefore, standardization of practices might enhance better comparisons between outcomes. In these settings, the Brazilian Society of Surgical Oncology considered it important to present a proposal for standardizing cytoreductive surgery plus hypertermic intraperitoneal chemotherapy procedures in Brazil, with a special focus on producing homogeneous data for the developing Brazilian register for peritoneal surface malignancies.